2012
DOI: 10.1007/s10856-012-4578-6
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of titanium oxide and hydroxyapatite as an artificial cornea skirt

Abstract: Keratoprosthetic devices are subject to chronic inflammatory, pathological processes and the external environment that affect their stability and biocompatibility with the ocular surface and adjacent ocular tissues. We compared the corrosion resistance property and tissue-implant reaction of titanium oxide (TiO(2)) with hydroxyapatite (HA) in artificial tear fluid and a rabbit skin implantation model. The dissolution properties of the implant surfaces were evaluated with scanning electronic microscope (SEM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…9,15 Bioactive materials, including glass and hydroxyapatite (HA) ceramics, have shown good tissue integration. 16,17 However, serious complications such as aqueous leakage, retroprosthetic membrane formation, and endophthalmitis are frequently observed due to the degradation of these bioactive materials. 9,15 Bioinert materials, such as titanium (Ti) or titanium alloys, aluminum, or their modified compounds have also been used as Kpro skirt materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9,15 Bioactive materials, including glass and hydroxyapatite (HA) ceramics, have shown good tissue integration. 16,17 However, serious complications such as aqueous leakage, retroprosthetic membrane formation, and endophthalmitis are frequently observed due to the degradation of these bioactive materials. 9,15 Bioinert materials, such as titanium (Ti) or titanium alloys, aluminum, or their modified compounds have also been used as Kpro skirt materials.…”
mentioning
confidence: 99%
“…18 We have previously shown that sintered titanium dioxide (TiO 2 ) exhibited excellent biocompatibility and corrosion resistance properties in an in vitro simulated ocular environment and in vivo animal model. 16,17 To further improve the biocompatibility and bactericidal properties of the implants, we functionalized the surface of TiO 2 with antimicrobial peptide coating. 19,20 The nonoxidized, metallic Ti has been used in the Boston KPro, due to its better compatibility compared to PMMA, 21 and the decreased formation of retroprosthetic membranes when Ti was used as a backing plate.…”
mentioning
confidence: 99%
“…The color is solely based on the controlled thickness of the Ti oxide layer. Characterization of the anodized Ti was undertaken using scanning electron microscopy, 9 XRD, 7 FTIR, 10 and AFM, 11 as previously described. High-resolution scanning electron microscopy images (10 nm) were acquired using the field emission scanning electron microscopy (FESEM) Ultra Plus (Carl Zeiss Microscopy GmbH, Jena, Germany) for surface morphology evaluation as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth underlining that the ideal implantation site for ophthalmic biomaterials is the eye with its unique physiological and microenvironmental characteristics; however, this requires the expertise and availability of an ophthalmic surgeon to perform operation, which can represent an additional difficulty in building interdisciplinary research teams. In order to simplify the experiments, some authors proposed a rabbit skin subcutaneous model to investigate the in vivo suitability of new keratoprosthetic biomaterials . Special care should be dedicated to the development of methods to correlate and interpret the results deriving from different in vivo studies, the selection of the most appropriate animal models and the sequence to follow in performing the experiments.…”
Section: Criteria and Guidelines For Selecting And Testing Suitable Bmentioning
confidence: 99%